(3GdEfbGP GdHMQj Ydi VhA CMcGe GdJTQjYGJ GdhWfjI hGdeYGgOGJ GdOhdjI (B/ s - (3SdWGf Hf aQGL QTjO GdSHjYi s; (3eMeO HgLJ YHOGddg Cejf bGjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3OGFeG eG jJeMhQ GdMOjK Yf GdSajfI HGYJHGQgG LGPHI dcGaI eSGFd heTGcd GdbGfhf GdHMQj ShGA aj Pdc GdbGfhf GdHMQj GdhWfj Ch GdbGfhf GdOhdj GdHMQj GdPj jgJe CSGSkG HJfXje GdedGMI GdOhdjI ef cGaI LhGfHgG HYO Cf JQGYi cd OhdI GdbhGYO GdOhdjI GdeJYGQa YdjgG hGdebHhdI YehekG hGJNGP GdNWhGJ GddGReI dJCcjO GMJQGegG (B. (3hJSJeO gPg GdOQGSI CgejJgG ef GdZGjI GdJj jSYi EdjgG GdHGMK dJhVjMgG hgj JCejf SdGeI GdSaf CKfGA QMdGJgG ef NWQ GdgdGc GdPj bO JJYQV dg fJjLI Gdbhi GdbgQjI Ch GdNWC GdHTQi aj GdHMGQ , hSYjkG hQGA gPg GdZGjI CNJGQ GdHGMK ehVhY (B:"(3GdEfbGP GdHMQj aj VhA CMcGe GdJTQjYGJ GdhWfjI hGdeYGgOGJ GdOhdjI(B" (3YfhGfkG dgPg GdOQGSI hPdc dCf GdEfbGP gh GdCSdhH GdCeKd dfLGI GdSaf hGdCTNGU GdehLhOjf Ydj eJfgG hGdHVGFY hGdCeJYI GdJj JMedgG ef GdgdGc YfO JYQVgG dchGQK HMQjI hCReGJ CKfGA JLhGdgG aj GdHMGQ hGdeMjWGJ Ch CKfGA JhGLOgG ONhdkG hNQhLkG aj GdehGfF GdHMQjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B390-397s
Keywords: (3GdbGfhf GdJLGQjs; (3GdEfbGP GdHMQjs; (3GdJTQjYGJ GdhWfjIs; (3GdeYGgOGJ GdOhdjIs; (3XGgQI GdfgHs; (3GdeSGYOI GdHMQjIs; (3GdGfbGP HYO GdJUGOes; (3GdYbhO GdahQjIs; (3GfbGP GdGehGds; (3GfbGP GdGQhGM GdHTQjIs; (3GdSafjI GdefbPIs; (3GfbGP GdSajfIs; (3GdMWGe GdHMQis; (3NOeGJ GdGfbGP s; (3GdSajfI GdeSJZjKIs; (3QHGf GdSajfIs; (3NOeGJ GdbWQ hGdGQTGOs; (3YbO GdbWQ GdHMQis; (3YbO GdGQTGO GdHMQis; (3GdfXe GdJTQjYjI GdHMQjIs; (3GdGYQGa hGdYGOGJ GdHMQjIs; (3eLgR GdSajfIs; (3ecGaGI GdGfbGP GdHMQis; (3YbO GddhjORs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs